2017
DOI: 10.1136/bmjopen-2016-014643
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and alcohol use among drug users receiving methadone maintenance treatment: a cross-sectional study in a rural prefecture of Yunnan Province, Southwest China

Abstract: ObjectiveTo estimate the prevalence of ever, current and heavy tobacco and alcohol use and their correlates among patients undergoing methadone maintenance treatment (MMT).DesignCross-sectional study.SettingThe study was conducted in all of the 5 MMT clinics in Dehong Prefecture, China.Participants2121 (81.6%) eligible MMT participants were included in the study population.AnalysisOrdinal logistic regression was used to estimate the ORs and their 95% CIs.ResultsThe overall prevalence of ever, current and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…For example, in rural Taiwan, Aboriginal Taiwanese chewed betel quid (i.e., typically areca nut and slaked lime wrapped in a betel leaf) more than their Chinese counterparts (Chen et al 2001). In a study of rural inhabitants of an area in southwest China, ethnic minorities (i.e., Jingpo and Dai) had a higher prevalence of alcohol use than Han Chinese (Duan et al 2017). In rural Bangladesh, some groups (Oraon and Santal) were more likely than other groups (Hindu and Muslim) to engage in regular consumption of arrack, an alcohol beverage typically made from palm and/or date juice (Uddin 2008).…”
Section: Health Disparities In Substance Use and Treatment Between Ramentioning
confidence: 99%
“…For example, in rural Taiwan, Aboriginal Taiwanese chewed betel quid (i.e., typically areca nut and slaked lime wrapped in a betel leaf) more than their Chinese counterparts (Chen et al 2001). In a study of rural inhabitants of an area in southwest China, ethnic minorities (i.e., Jingpo and Dai) had a higher prevalence of alcohol use than Han Chinese (Duan et al 2017). In rural Bangladesh, some groups (Oraon and Santal) were more likely than other groups (Hindu and Muslim) to engage in regular consumption of arrack, an alcohol beverage typically made from palm and/or date juice (Uddin 2008).…”
Section: Health Disparities In Substance Use and Treatment Between Ramentioning
confidence: 99%
“…Meanwhile, Huyen et al in Vietnam suggested that being employed was a negative predictor of level of nicotine dependence ( Do et al, 2017 ). Patients with HIV positive were found to have lower likelihood of smoking and alcohol abusing than those with HIV negative ( Do et al, 2017 , Duan et al, 2017 ). With these variabilities of potential markers for predicting alcohol and smoking addicts among MMT patients, understanding the factors associated with these risk behaviors is essential in order to ensure the effectiveness of MMT program.…”
Section: Introductionmentioning
confidence: 96%
“…Some studies found that people with higher duration of MMT were less likely to drink hazardously or smoking heavily ( Baran-Furga et al, 2005 , Do et al, 2017 , Duan et al, 2017 ), while others indicates no association ( Stark & Campbell, 1993b ). Song Duan et al (2017) in China found that male, older and less educated patients had higher likelihood to be heavy smokers and hazardous drinkers ( Duan et al, 2017 ). Meanwhile, Huyen et al in Vietnam suggested that being employed was a negative predictor of level of nicotine dependence ( Do et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is essential to understand how PWUD differently perceive danger and risk-taking behaviors during an epidemic, making them more risk averse ( Manfredi & D’Onofrio, 2013 ; Rhodes, 1997 ). PWUD have a higher rate of smoking and different studies estimated the current smoking rate of more than 70% among them ( Duan et al, 2017 ; Sutherland et al, 2016 ; Weinberger, Gbedemah, & Goodwin, 2017 ). Several studies found smoking a significant risk factor for Middle East Respiratory Syndrome (MERS) transmission ( Alraddadi et al, 2016 ; Nam, Park, Ki, Yeon, Kim, & Kim, 2017 ; Sherbini Iskandrani, Kharaba, Khalid, Abduljawad, & Hamdan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%